2005
DOI: 10.1103/physrevb.71.054509
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic nonmonotonic behavior of the superconducting critical current in thinYBa2Cu3O7δ

Abstract: The critical current density of epitaxial YBa 2 Cu 3 O 7-δ (YBCO) films grown on vicinal

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
4
16
1
Order By: Relevance
“…In addition, anti-phase boundaries (APBs) can be expected to occur in a vicinal film. In transport measurements on YBCO films grown on substrates with miscut angles of 4 and 8 APBs were identified as the reason for different values in the L and T direction [11]. In spite of this in the present study no difference was observed in of the two tracks.…”
Section: Resultscontrasting
confidence: 78%
“…In addition, anti-phase boundaries (APBs) can be expected to occur in a vicinal film. In transport measurements on YBCO films grown on substrates with miscut angles of 4 and 8 APBs were identified as the reason for different values in the L and T direction [11]. In spite of this in the present study no difference was observed in of the two tracks.…”
Section: Resultscontrasting
confidence: 78%
“…for all the films. Maximum critical current densities in this range were also reported by other authors [14,15], although larger j S were measured on films deposited either on vicinal substrates [14] or on nanobridges [16,17] In order to confirm the validity of our determination of the T c profiles, the oxygen content of film B, whose characteristics are reported in Table 1, was measured by Non Rutherford Elastic Resonance Scattering (NRERS) by J.Siejka (INSP-Paris) [19]. The oxygen content of film B was found to be depth dependent.…”
Section: Determination Of the T C Profilessupporting
confidence: 89%
“…12,21 The rapid falloff at higher fields and vanishing of J c at B irr is well-represented by the last factor, chosen with a physically reasonable fixed exponent of 2. model Eq. ͑1͒ is also exhibited in the Fig.…”
Section: Resultsmentioning
confidence: 99%